PENGARUH PENGGUNAAN MEDIA FLASH CARD TERHADAP KEMAMPUAN MEMBACA PERMULAAN PADA PEMBELAJARAN BAHASA INDONESIA KELAS I SDI MANUNAI - Agustina Sofia Gelu; Sonya Kristiani Maria; Yohanes Ehe Lawotan (STKIP Subang, 2026)
This study was motivated by the low level of beginning reading skills among Grade I students in Indonesian language learning at SDI Manunai. One effort that can be made to improve students' beginning reading skills is the use of flash card media. This research employed a quantitative approach with an experimental research design using a one-group pretest-posttest design. The population of this study consisted of all Grade I students of SDI Manunai, who also served as the research sample, totaling 18 students. The data collection techniques used were tests, observation, and documentation. The research instruments included pretest and posttest questions as well as observation sheets. The data analysis techniques used were the normality test and the paired sample t-test hypothesis test with the assistance of SPSS version 21. The results showed that the average pretest score of 53.89 increased to 93.33 in the posttest. The hypothesis test results indicated a Sig. (2-tailed) value of 0.000 < 0.05, meaning that H₀ was rejected and Hₐ was accepted. In addition, the observation results showed an average achievement rate of 96.43%, which was categorized as very good. Therefore, it can be concluded that the use of flash card media has a significant effect on students' beginning reading skills in Indonesian language learning for Grade I students at SDI Manunai.